Dynamic carbon emission management - Maria Cecilia Bustamante; Francesca Zucchi (European Central Bank (ECB), 2024)
The control of carbon emissions by policymakers poses the corporate challenge of developing an optimal carbon management policy. We provide a unified model that characterizes how firms should optimally manage emissions through production, green investment, and the trading of carbon credits. We show that carbon pricing reduces firms' emissions but also induces firms to tilt towards more immediate yet transient types of green investment-such as abatement as opposed to innovation-as it becomes costlier to comply. Green innovation subsidies mitigate this effect and complement carbon pricing in ensuring innovation-driven sustainability. Perhaps surprisingly, we show that carbon regulation need not reduce firm value.
Keywords: G30; G31; G12; D62; O33; 330; Carbon pricing; Carbon Emissions; Carbon Abatement; Green Innovation; Sustainability